Memories of being injured and patients' care trajectory after physical trauma - Bergbom Ingegerd; Plos Kaety; Ringdal Mona (BMC, 2008)
Abstract Background The purpose of this study was to acquire a deeper understanding of patients' memories of being injured and the trajectory of care before, during and after their Intensive Care Unit (ICU) stay. Methods Interviews were conducted with eighteen informants who after physical trauma had been cared for in the ICU. The interviews were analyzed by using a phenomenological hermeneutical method. Results The memories of injury during the trajectory of care are illustrated in a figure in which the injured informants have memories from five scenes; the scene of the accident, emergency unit, ICU, nursing ward and of coming home. Twelve subthemes were abstracted and four themes emerged; a surrealistic world, an injured body, care, and gratitude for life. After the accident, a "surrealistic world" appeared along with bad memories of being in a floating existence where plans had to be changed. This world was unfamiliar, sometimes including delusional and fragmentary memories from the ICU, and it was experienced as uncontrollable. They felt connected to an "injured body", experiencing bad memories from the ICU of being injured, from the nursing ward of simply enduring and of being in a No Man's Land when coming home; their lives had become limited. At the same time they were "connected to care" with good memories of receiving attention from others at the scene of the accident, being taken cared of at the emergency unit and cared for in the ICU. This care made them realise that people are responsible for each other, and they felt comforted but also vulnerable. Finally, they experienced "gratitude for life". This included good memories of being loved together with support from their families at the ICU, wanting to win life back at the nursing ward and acceptance when returning home. The support from their families made them realise that they fit in just as they are. Conclusion When bad memories of a surrealistic world and of being injured are balanced by good ones of care and love with a gratitude for life, there are more possibilities to move on despite an uncertain future following the injury.